Optimal Treatment in Parkinson’s Disease: Pharmacotherapy and Practical Tips - Kulkantrakorn, Kongkiat (The Bangkok Medical Journal, 2015)
Parkinson’s disease, a common neurodegenerative disorder, is treatable. The currenttreatment strategy is focused on dopamine replacement. Every patient will eventuallyreceive levodopa which is the gold standard therapy, but it is associated with motorcomplication in a later phase. Using other dopaminergic medications as the fi rst linetreatment to avoid levodopa usage may reduce motor complication, but they are lesseffi cacious in symptomatic control. However, in the later stage of the disease, patientsoften need other medications to optimize dopaminergic transmission. Dopamine agonist(DA), monoamine oxidase inhibitor (MAO-BI) and catechol-o-methyl-transferaseinhibitors (COMTI) are standard adjunctive medications in patients who have levodopa-induced motor complication.